Studi Komparasi Kualitas Hidup dan Kinerja pada Karyawan dengan Model Kerja Hybrid dan Full-Remote di Yayasan XYZ Jakarta Selatan - Fenti Cahyani; Desyawati Utami; Izzatu Millah; Mugi Wahidin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The advancement of information and communication technology, along with post-pandemic changes, has transformed global work structures. Full-remote and hybrid work models remain widely implemented, offering both conveniences and challenges for employees. This study compares the quality of life and performance of full-remote and hybrid employees at Yayasan XYZ, South Jakarta. Using a quantitative method with a cross-sectional design, data were collected from 48 purposively sampled employees via questionnaires. The research results indicate that, based on the average scores obtained, full-remote employees exhibit a higher quality of life in the physical, psychological, and environmental domains, whereas hybrid employees excel in the social domain. The comparative analysis of quality of life revealed no significant differences between these two work models. In terms of performance, hybrid employees demonstrated higher productivity levels than full-remote employees, with an average score of 9.22 for full-remote and 9.64 for hybrid work models. However, the comparative analysis of performance also indicated no statistically significant differences between the two models. In conclusion, while there are variations in the experiences of employees working under full-remote and hybrid models, the comparative analysis confirms that there are no significant differences in terms of quality of life and performance between these two work models. The results of this study are expected to serve as a basis for Yayasan XYZ in formulating optimal work model policies to ensure employee well-being and productivity